Consciousness of the consequences of smoking cigarettes and the prevalence of cigarette smoking among medical students - Radzka, Agnieszka; Ciechański, Krystian; Tkaczyk, Jędrzej; Brożyna, Klaudia; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2018)
Cigarettes are composed of toxic substances that result in the development of chronic obstructive pulmonary disease (COPD) and cardiovascular diseases. Smoking is also a risk factor of many cancers. Among the billions of smokers in the world, many of them are doctors and medical students - people who realize the importance of negative consequences of this addiction. We made an anonymous questionnaire, which contained 28 original questions and was published on the Internet to find out how many students of Medical Universities in Poland are addicted to tobacco and if they are aware of the consequences of their addiction. Papierosy składają się z wielu toksycznych substancji, powodują rozwój POChP, chorób sercowo-naczyniowych, a także są predykatorami wielu nowotworów. Wśród miliardów palaczy na świecie są lekarze, studenci medycyny, ludzie, którzy zdają sobie sprawę z wagi komplikacji tego uzależnienia. Przeprowadzono anonimową ankietę, która zawierała 28 oryginalnych pytań i została opublikowana w internecie, aby sprawdzić, ilu studentów uniwersytetów medycznych w Polsce jest uzależnionych od tytoniu i czy są oni świadomi konsekwencji uzależnienia.